SOME ASPECTS OF THE LIFE HISTORY AND MORPHOLOGY OF STRONGYLOIDES OPHIDIAE PEREIRA, 1929 (RHABDITIDA: STRONGYLOIDIDAE) IN LIOPHIS MILIARIS (SQUAMATA: DIPSADIDAE) - Tenório Mati, Vitor Luís (2014)
Snake strongyloidiasis was studied in specimens of Liophis miliaris that were experimentally andnaturally infected with Strongyloides ophidiae. Fecal analysis indicated that S. ophidiae parasitism could last more than three months in the host. Parasite development occurred in snakes infected via the subcutaneous route, and the prepatent period of the infection was seven days. These snakes exhibited significant clinical signs and none of the stool analyses were negative. However, in naturally infected snakes, intermittent results were found in serial fecal tests. A direct cycle of development was predominant in stool cultures from snakes with both types of infection, and attempts to eliminate the parasite with ivermectin failed. Enteritis was a common gross finding in dead snakes. As previous descriptions of S. ophidiae have presented certain shortcomings, a morphological analysis of the parasite was performed, and clear differences between this South American species and S. serpentis from North America were observed. There has been taxonomic uncertainty in the literature as to whether these species of Strongyloides are indeed distinct. The observations made in L. miliaris provide experimental evidence that the biology of the parasite in heterothermic hosts is similar to that observed in mammals, and this species may be considered a potential dipsadid model for the study of snake strongyloidiasis.